South Africa : Technical Assistance Report-Revenue Administration Gap Analysis Program-The Value-Added Tax Gap. (IMF Staff Country Reports; Country Report, 2015)
This Technical Assistance Report discusses the results of applying the value-added tax (VAT) gap estimation methodology of the Revenue Administration Gap Analysis Program (RA-GAP) to South Africa for the period 2007-12. It is found that the compliance gap is estimated to be between 5 percent and 10 percent of potential VAT revenues during the period 2007-12, and peaking in 2008 and 2009. The estimated compliance gap for VAT in South Africa between 2007 and 2012 is hump-shaped. The results also reveal that the level of the VAT policy gap in South Africa is low by international standards, owing to its simple VAT policy structure.